(untitled) (Scientia Agricola, 2015)
The change of grape (Vitis vinifera) harvest from summer to winter through double pruning management has improved the fine wine quality in southern Brazil. High altitude, late cultivar and grafting combination all need to be investigated to optimize this new viticulture management. For this purpose, this study was carried out during the 2011 and 2012 growing seasons in a high altitude region of the state of Minas Gerais, Brazil, using eight grafting combinations for five year old Cabernet Sauvignon vines. The stem water potential, photosynthetic rate and stomatal conductance were not affected by rootstock type. The rootstocks IAC 766 and 101-14 induced, respectively, the highest and lowest vegetative vigor in Cabernet Sauvignon, as shown by leaf area and pruning weight. In the 2011 growing season, the leaf chlorophyll contents were increased in IAC 766, whereas vines grafted onto 101-14 accumulated more leaf starch, probably due to reduced vegetative and reproductive growth. In general, rootstocks K5BB, 1045P, SO4 and IAC 766 had the highest yield as compared to 1103P and 101-14. Berries from the grapevine with the highest yield did not differ in pH, total soluble solids and acidity. The rootstocks did not influence the anthocyanins and total phenols in both growing seasons. Quality parameters were better in the 2011 than in the 2012 growing season due to better climatic conditions, mainly less rainfall. The best performance of Cabernet Sauvignon was achieved when grafted onto K5BB, 1045P, SO4 and IAC 766 rootstocks.